How to talk to anyone at work: 72 little tricks for big success communicating on the job - Lowndes, Leil (New York : McGraw-Hill Education, 2019)
"From the bestselling author of How to Talk to Anyone comes a book dedicated to helping business professionals at any level communicate for success on the job You face tough communication challenges every day at work, both in person and online. Here are immediate, effective, eye-opening actions you can take to resolve those infuriating problems. You will find stories and examples drawn from corporate communications consultant Leil Lowndes's more than 20 years of training business professionals, from entry-level new hires to CEOs. To succeed today, you must exhibit these crucial qualities, the 5 Cs: CONFIDENCE 10 ways to show your boss and colleagues you are 100 percent self-assured and can achieve whatever you want -- and reinforce this image throughout your entire working relationship CARING 14 strategies to demonstrate you care about your colleagues and the company because "people don't care how much you know until they know how much you care" CLARITY 12 techniques to get your ideas across clearly -- and ensure you understand everybody you work with CREDIBILITY14 methods to win the trust and respect of everyone at your company -- and impress people who find you on the web COEXISTENCE (WITH CRUEL BOSSES & CRAZY COLLEAGUES)21 tactics to confront the number one workplace nightmare and come out shining Plus one final astonishing technique to guarantee success and happiness in your professional life. After you've mastered the unique "bag of little tricks" in this book, you will know How to Talk to Anyone at Work!"--
"Different tips and tricks for how to talk to anyone at work"--
Includes bibliographical references.
AAL
Complimentary copy
Keywords: Business communication; BUSINESS & ECONOMICS / Business Communication / General